1998
DOI: 10.1080/13571519884495
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Market Concentration and Horizontal Mergers on Hospital Costs and Prices

Abstract: Antitrust advocates believe that horizontal consolidation in hospital markets can reduce competition and increase prices while merger advocates believe it can benefit consumers by reducing service duplication. This study analyzed the market conditions, operating characteristics, and costs and prices of approximately 3500 short-term general hospitals (including 112 within-market-area mergers) from 1986 to 1994 to investigate the effects of market concentration, hospital mergers, and managed care penetration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 18 publications
3
82
1
2
Order By: Relevance
“…Research also posits that the lack of conflict and the presence of administrative hierarchies make initial consolidation achievable (Ibid). Again, these initial savings tend to be small in magnitude (Connor et al, 1998;Lesser & Brewster, 2001) and may simply be one-shot savings (Bazzoli et al, 2004). The results of this thesis clearly confirm previous findings of "small initial wins" The achieved cost savings for the first year were -as previously mentioned -relatively small by average industry standards.…”
Section: Managerial Hubris and Managerial Worksupporting
confidence: 80%
See 3 more Smart Citations
“…Research also posits that the lack of conflict and the presence of administrative hierarchies make initial consolidation achievable (Ibid). Again, these initial savings tend to be small in magnitude (Connor et al, 1998;Lesser & Brewster, 2001) and may simply be one-shot savings (Bazzoli et al, 2004). The results of this thesis clearly confirm previous findings of "small initial wins" The achieved cost savings for the first year were -as previously mentioned -relatively small by average industry standards.…”
Section: Managerial Hubris and Managerial Worksupporting
confidence: 80%
“…legal mergers under one license and owner) and not include those with multihospital affiliations, one would observe more consistency in results. Namely, several studies on full mergers per se have achieved positive cost savings (Alexander et al, 1996;Connor et al, 1998;Dranove, 1998;Eberhardt, 2001;Lesser & Brewster, 2001). All studies that have found no costs savings or cost increases examined multi-hospital arrangements (Dranove et al, 1996).…”
Section: Obstacles When Integrating Clinical Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies conclude that mergers result in higher prices, potentially blunting savings achieved through managed care (Simpson and Shin 1998;Keeler, Melnick, and Zwanziger 1999). Other studies find that mergers lower prices, consistent with the thesis that they lead to economies of scale and the reduction of excess capacity (Connor and Feldman 1998;Connor, Feldman, and Dowd 1998). Various studies also report conflicting findings about whether the profit-status of the two merging hospitals affects prices (see for example Lynk [1995] and responses by Dranove and Ludwick [1999], Keeler, Melnick, and Zwanziger [1999], and Simpson and Shin [1998]).…”
Section: Introductionmentioning
confidence: 77%